Changes in self-reported physical and mental health, behaviour and economic status among adults by known seropositivity and sociodemographic factors before and after the COVID-19 pandemic outbreak in Ischgl, Austria - Bates, Katie; Borena, Wegene; McKee, Martin; Hayek, Lore; Bouanchaud, Paul; Bánki, Zoltán; Riepler, Lydia; Rössler, Annika; Falkensammer, Barbara; Paetzold, Jörg; Walser, Andreas; Schönherr, Sebastian; et al. (Frontiers in Public Health, 2025)
IntroductionIn early March 2020, a SARS-CoV-2 outbreak occurred in the ski resort of Ischgl, in Austria. After an initial seroprevalence study in April 2020, a follow-up study in November 2020 showed persistence of high levels of seropositivity. The impacts of SARS-CoV-2 infections and non-pharmaceutical interventions required to reduce transmission were wide-ranging, including worsened mental and physical health and economic damage.MethodsWe analysed data from the Ischgl follow-up study. Of the 1,259 adults that participated in the Ischgl-1 study (Ischgl-1), 801 were followed-up. Seropositivity was defined using presence of binding and neutralizing antibodies at Ischgl-1. At follow-up, 7 months later (Ischgl-2), participants reported changes to self-rated mental and physical health, physical activity, alcohol consumption, smoking and economic status. Changes were compared by serological status, using multivariable logistic and multinomial regression models, where appropriate, and adjusting for factors including age, sex, and morbidity.Results1 in 2 participants reported experiencing a moderate or severe impact of the pandemic. One fifth of participants reported a worsening in their mental health from November 2019 to November 2020; women and participants aged ≥35 to <70 years were disproportionately affected. Seropositivity was associated with a decline in physical health but no decline in mental health or behaviour changes. Very few participants reported any changes in behaviours. The overriding impact the population of Ischgl was economic—50% of participants reported a worsening of their professional and/or financial situation. Declines in self-reported mental health were associated with the overall experience of the pandemic and economic factors.ConclusionThe population of Ischgl demonstrated a high level of resilience to the pandemic as measured by health. However, certain segments of the population were disproportionately affected, particularly with regard to mental health and economic wellbeing. Future pandemic preparedness must consider how pandemic mitigation strategies can be responsive to context and the wider impacts on mental health and social and economic wellbeing while minimising mortality and safeguarding health systems.